A reduced vernalization requirement is a key component of the early-bolting trait in globe artichoke (Cynara cardunculus var. scolymus) - Rick Berentsen; Reyes Benlloch; Peter Visser; Francisco Madueño; Vicente Balanzà (iScience, 2024)
Summary: Early bolting is a major breeding objective for globe artichoke (Cynara cardunculus var. scolymus L.). It has been suggested that globe artichoke bolting time is linked to a vernalization requirement, although environmental conditions under which vernalized plants and controls have been grown may not always allow for proper comparison. Here, we defined morphological markers to monitor the vegetative-to-reproductive phase transition at the shoot apex and linked these to expression changes of homologs of key Arabidopsis flowering regulators SOC1, FUL, and AP1. Importantly, we developed an experimental setup where control and vernalized plants grow under comparable conditions. These tools together allowed for comparison of the vegetative-to-reproductive phase transition between early- and late-bolting genotypes and how they respond to vernalization. Our results show that vernalization requirement is significantly lower in early-bolting genotypes, supporting the hypothesis that the early-bolting trait is at least partly underlain by alterations in the network controlling vernalization response.